Densitometric analysis of the autogenous demineralized dentin matrix on the dental socket wound healing process in humans - Gomes, Mônica Fernandes; de Abreu, Paula Pinheiro [UNESP]; Cantarelli Morosolli, Aline Rose [UNESP]; Araújo, Marcelo Marotta [UNESP]; Vilela Goulart, Maria das Graças [UNESP] (FapUNIFESP (SciELO), 2006)
The aim of this study was to evaluate the effects of the autogenous demineralized dentin matrix (ADDM) on the third molar socket wound healing process in humans, using the guided bone regeneration technique and a polytetrafluoroethylene barrier (PTFE). Twenty-seven dental sockets were divided into three groups: dental socket (Control), dental socket with PTFE barrier (PTFE), and dental socket with ADDM slices associated to PTFE banier (ADDM + PTFE). The dental sockets were submitted to radiographic bone densitometry analysis and statistical analysis on the 15th, 30th, 60th and 90th days using analysis of variance (ANOVA) and Tukey's test (p ≤ 0.05). The radiographic analysis of the ADDM + PTFE group showed greater homogeneity of bone radiopacity than the Control group and the PTFE group, during all the observation times. The dentin matrix gradually disappeared from the dental socket during the course of the repair process, suggesting its resorption during the bone remodeling process. It was concluded that the radiographic bone density of the dental sockets treated with ADDM was similar to that of the surrounding normal bone on the 90th day. The ADDM was biocompatible with the bone tissue of the surgical wounds of human dental sockets. The radiographic analysis revealed that the repair process was discreetly faster in the ADDM + PTFE group than in the Control and PTFE groups, although the difference was not statistically significant. In addition, the radiographic image of the ADDM + PTFE group suggested that its bone architecture was better than that of the Control and PFTE groups.
Keywords: Bone regeneration; Dentin; Tissue engineering; biomaterial; Demineralized Dentin Matrix; politef; unclassified drug; adolescent; adult; analysis of variance; bone density; bone matrix; bone regeneration; comparative study; dentin; drug effect; female; human; male; methodology; molar tooth; periodontics; physiology; radiography; standard; tissue engineering; tooth extraction; tooth implantation; tooth socket; wound healing; Adolescent; Adult; Analysis of Variance; Biocompatible Materials; Bone Density; Bone Matrix; Bone Regeneration; Dental Implants; Female; Guided Tissue Regeneration, Periodontal; Humans; Male; Molar, Third; Polytetrafluoroethylene; Tissue Engineering; Tooth Extraction; Tooth Socket; Wound Healing